Transfer and adaptation of a drug recovery model from San Patrignano, Italy to River Garden, Scotland: a qualitative study. (4th March 2023) - Devlin, Alison M.; Wight, Daniel
Abstract: Innovation in addiction recovery in Scotland includes the transfer of effective models from other countries, such as San Patrignano, Italy and Basta, Sweden. Independence from Drugs and Alcohol Scotland (IFDAS) was founded to develop a new model for Scotland, based on social enterprise. Drawing on the San Patrignano programme theory, this prospective study investigates IFDAS stakeholders' perspectives on which mechanisms should be transferred, and which require adaptation of the delivery mode, for the Scottish context. Data collection included interviews with ten stakeholders with expertise including: drugs policy, social enterprise, alcohol and drug partnership practice and therapeutic community methods. Drawing on realist principles, data were analysed using inductive and deductive approaches and synthesised using frameworks. San Patrignano mechanisms identified for transfer include: the need for motivation, recovery peer mentors, visionary leadership and social enterprise. Adaptations from Basta include: extending abstinence to alcohol and creating a smaller, semi-permeable, residential community. Further adaptations to mechanism delivery include a 'step-wise' model of housing and work. Scottish contextual factors shaping adaptations include: the culture of alcohol misuse, social care standards, housing regulations and socio-cultural acceptability. This study contributes to the evidence on international transfer and adaptation of complex interventions and documents stakeholders' theory-informed decision making in the development of a new Scottish recovery model.